Evaluasi Pelaksanaan Program Sumbar Sadar Vaksin di Puskesmas Seberang Padang - Riandi, Mutiara; Magriasti, Lince (Policy, Law and Political Research Center, 2023)
This study aims to analyze the Evaluation of Implementation Sumbar Sadar Vaksin Program (Sumdarsin) by the Seberang Padang Health Center. This type of research is qualitative. The results of this study indicate that the analysis of several aspects for the Evaluation of Implementation Sumbar Sadar Vaksin Program (Sumdarsin) by the Seberang Padang Health Center includes reducing the transmission or transmission of Covid-19, reducing morbidity and mortality due to Covid-19, and protecting the public from covid-19 to remain socially and economically productive. The obstacles found in the Evaluation of Implementation Sumbar Sadar Vaksin Program (Sumdarsin) by the Seberang Padang Health Center include limited socialization of vaccinations to the community, public distrust of vaccines, and the lack of available facilities.